THE PROBLEM OF FORMATION OF AN INDIVIDUAL’S PROFESSIONAL AWARENESS AT THE STAGE OF PROFESSIONAL CHOICES - Omelchenko, Maryna (PSYCHOLOGICAL JOURNAL, 2019)
The article studies formation of an individual’s professional awareness at the stage of professional choices. Professional formation in psychology is considered, as a rule, in the context professional development and provision of successful and effective professional work. The analytical review of scientific sources allowed us to identify the basic elements for decision making on professional choices, which can be represented by the following definitions: an agent of a professional choice; formation of professional awareness; personal values; personal meanings; professional ideas; a personal model of a profession; expectations and forecasts; a professional choice. These elements have been ordered and presented in the form of a psychological mechanism for a choice of profession. An agent’s professional ideas always determine his/her degree of personal acceptance of a profession. If there are possible alternatives for professional choices, then a choosing agent consider the professional reality through own system of personal values. By making hypothetically a professional choice, an individual takes into account personal significance of certain aspects of the considered profession. Thus, a choosing agent approaches to the next stage – the construction of a personal model of work, which, in its turn, determines, in a certain way, personal meanings and certain expectations and vision of professional prospects in the agent’s consciousness. At this stage a real professional choice is made, which determines the course of professional awareness formation and the process of an individual’s professional development as a specialist. The development of a professional choice mechanism requires the compilation and implementation of special training programs aimed at improving the quality indicators of such aspects of professional awareness as professional ideas, reflection, values and motives, emotions to optimize professional choices, to regulate professional relations and to improve the quality of professional actions.